RADIOLOGICAL ASPECTS OF HEMORRHAGE INTO PITUITARY ADENOMAS - M. A. Kutin; B. A. Kadashev; P. L. Kalinin; L. I. Astaf’eva; E. V. Sidoruk; D. V. Fomichev; O. I. Sharipov; A. M. Turkin; E. I. Shul’ts; N. I. Mikhaylov (Вестник рентгенологии и радиологии)
Objective. To reveal the characteristic radiological features of pituitary apoplexy, which are able to influence its treatment policy. Material and methods. 82 patients with pituitary apoplexy were analyzed. Surgery was not performed in 37 cases and its need disappeared during medical treatment. 45 patients were operated on in different periods after the onset of hemorrhage. The characteristics of MR images of a pituitary apoplexy focus and the likelihood of complete tumor resorption were assessed. Results. Cystic cavities in the tumor stroma were more frequently found at 3 months after the onset of hemorrhage. Complete resorption occurred mainly in pituitary adenomas measuring < 40 mm in size. Tumor resorption occurred more often in diffuse infiltration of the tumor stroma. Conclusion. Medical therapy may be the mainstay of treatment for pituitary apoplexy in tumors < 40 mm with a hemorrhage duration of less than 3 months if cysts are absent in the stroma, regardless of a patient’s status. The probability of pituitary function recovery in this case was 87.5%.